MEWASPADAI VIRUS LGBT PADA PENDIDIKAN ANAK - Hikmatur Rahmah (Paedagogia: Jurnal Pendidikan, 2018)
LGBT (Lesbian, Gay, Bisexual and Transgender) is a frightening epidemic of society, especially in Indonesia. The epidemic also infects most children and adolescents. So as educators, both parents and teachers should pay particular attention to the symptoms that cause virus LGBT in the community, especially in children's education. Because it is against the nature, norms, customs, religion and morals of humanity. Moreover, LGBT's behavior is not a disease transmitted through genes or disorders, but more to the consequences mistakes and erros of children’s education.